2014
DOI: 10.1073/pnas.1403576111
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for activity-dependent glucose phosphorylation in neurons with implications for the astrocyte-to-neuron lactate shuttle

Abstract: Previous 13C magnetic resonance spectroscopy experiments have shown that over a wide range of neuronal activity, approximately one molecule of glucose is oxidized for every molecule of glutamate released by neurons and recycled through astrocytic glutamine. The measured kinetics were shown to agree with the stoichiometry of a hypothetical astrocyte-to-neuron lactate shuttle model, which predicted negligible functional neuronal uptake of glucose. To test this model, we measured the uptake and phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 55 publications
5
164
0
2
Order By: Relevance
“…Much of this ATP may be generated from lactate produced by adjacent glial cells and then imported into neurons via the astrocyteneuron lactate shuttle, where it is converted into pyruvate (28,59). However, recent evidence suggests that neurons (not astrocytes) directly metabolize much of the glucose entering the brain (60,61), suggesting that glycolysis may actually contribute more to supporting neuronal energy needs than previously suspected. Importantly, we must better understand the role of energy failure in neurodegeneration because mitochondria have other functions; they buffer calcium, produce reactive oxygen species, synthesize lipids, and regulate apoptosis (62).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this ATP may be generated from lactate produced by adjacent glial cells and then imported into neurons via the astrocyteneuron lactate shuttle, where it is converted into pyruvate (28,59). However, recent evidence suggests that neurons (not astrocytes) directly metabolize much of the glucose entering the brain (60,61), suggesting that glycolysis may actually contribute more to supporting neuronal energy needs than previously suspected. Importantly, we must better understand the role of energy failure in neurodegeneration because mitochondria have other functions; they buffer calcium, produce reactive oxygen species, synthesize lipids, and regulate apoptosis (62).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, a well-known proposal is that during brain activation, lactate is mainly produced by astrocytes, and consumed in neurons [33,48]. However, other studies have concluded that neurons still consume glucose during brain activation, and that the excess of lactate produced is probably removed from the brain through the circulation [45,46,49,50]. The results of Bak et al [28,29] show that neurons may be one of the sites of lactate production during activation, perhaps due to intermittent MAS inhibition under high activating conditions, consistent with the role of matrix Ca 2?…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 98%
“…An important role for neuronal glycolysis as a source of the reducing equivalents is supported by our recent findings of significant activity-dependent glucose phosphorylation in nerve terminals in vivo. 40 For the awake rat cortex oxidizing ketone bodies at the maximum (saturating) rate of B0.7 mmol/g per minute, V pdhN would be 1.12 À 0.70 ¼ 0.42 mmol/g per minute. With V cyc ¼ 0.55 mmol/g per minute, V pdhN :V cyc B0.76:1, which is lower than the 2:1 ratio found between DV tcaN and DV cyc , reflecting the substantial contribution of BHB to total neuronal metabolism under saturating conditions.…”
Section: Implications Of Ketone Body Oxidation For Models Of Neuroenementioning
confidence: 99%